Introduction to clinical mental health counseling: contemporary issues - Watson, Joshua C (Sage, 2020)
Introduction to Clinical Mental Health Counseling presents a broad overview of the field of clinical mental health and provides students with the knowledge and skills to successfully put theory into practice in real-world settings. Drawing from their experience as clinicians, authors Joshua C. Watson and Michael K. Schmit cover the foundations of clinical mental health counseling along with current issues, trends, and population-specific considerations. The text introduces students to emerging paradigms in the field such as mindfulness, behavioral medicine, neuroscience, recovery-oriented care, provider care, person-centered treatment planning, and holistic wellness, while emphasizing the importance of selecting evidence-based practices appropriate for specific clients, issues, and settings. Aligned with 2016 CACREP Standards and offering practical activities and case examples, the text will prepare future counselors for the realities of clinical practice.